UJI KELAYAKAN PHANTOM LENGAN UNTUK PEMASANGAN KB IMPLAN DI LABORATORIUM KEBIDANAN POLTEKKES KEMENKES SORONG - Dian Kartikasari; Rico G Latumahina (LPPM Universitas Abdurrab, 2025)
As part of their training to provide family planning services, midwife students should be able to insert and remove sub cutaneous contraceptive implant. One method of long-term birth control is the use of a contraceptive implant, which releases levonogestrel over time. Placing this 3–4 cm long and 0.2 cm wide silicone capsule beneath the skin on the inside of the upper arm is one method of preventing pregnancy. Students use a foam-coated- rubber upper arm model for hands-on practice inserting and removing contraceptive implants in the lab. Because this phantom is missing an upper arm, students have a harder time pinpointing the precise spot to put a contraceptive implant. This project aims to construct a comprehensive arm phantom that can assess the layers of skin and muscle for the purpose of placing contraceptive implants. This research is an research and development study. The research was carried out for 9 months from January to September 2024. To analyse the data, we first used a Likert scale to quantify the qualitative evaluations, then averaged the scores, and finally returned to the qualitative values. In order to determine if it was feasible, we compared the respondents' evaluation ratings to the ideal scores. With a mean score of 6.46 (range: 6.15-7.00), respondents highly agreed that the instrument is feasible to use, according to the data. The product's viability was determined to be 91.76%. Developing tool features needs to be carried out so that the tool can be used for various other functions as a teaching aid for other practicums related to midwifery clinical skills.